CEO Turnover and Market Reaction in Indonesia - Setiawan, Doddy; Kee Phua, Lian; Chee, Hong Kok (UI Scholars Hub, 2013)
This research examines Chief Executive Officer (CEO) turnover and market reaction in Indonesia. The sample of this research consists of 213 CEO turnover announcements for Indonesia Stock Exchange during 2000–2010 period. T-tests were used to investigate the effect of CEO turnover announcement on abnormal stock return during the event windows periods. The results of this research show that there is positive reaction on the CEO turnover announcements. This research considers both routine and non routine CEO turnover processes. This research finds that both turnover processes have information content to investor. This research also finds positive reaction on the announcements of outsider incoming CEO, while investors do not react on the announcement of insider incoming CEO. Thus, this research provides evidence that CEO turnover announcement have information content.